Is Historical Study of Nahwu on Madrasah Basra and Kufa Important to Teach? The Analysis of Opinion on Indonesian AFL Students - Ulfa febriyanti; Maman Abdurrahman; Asep Sopian (Universitas Islam Negeri Palangka Raya, 2021)
The knowledge of nahwu has been taught in many universities in Indonesia. However, the study of the nahwu taught is still limited to a study oriented to the science of tools in learning Arabic and ignores historical, theoretical aspects such as Madrasah Basra and Kufa. Therefore, this study aims to prove whether this historical, academic study is essential to be taught to Indonesian AFL students. This research uses a quantitative approach with a descriptive type. The questionnaire was given to several 20 fifth-semester AFL students with three open-ended questions about their knowledge of Madrasah Basra and Kufa. The results of this study indicate that 60% of students are familiar with Madrasah Basrah and Kufa. Most of them hear about Madrasah Basrah and Kufa for the first time in college (75%), in pesantren (8.3%), on the internet (8.3%), at high school (8.3%), and from the sermon (8.3%.). Moreover, the students generally know about Madrasah Basrah and Kufa's differences, but it is only limited to the differences in terms and I'rab. Therefore, the learning of nahwu needs to be developed by paying attention to the historical aspects of the nahwu development, especially the differences from Madrasah Basrah and Kufa.